RGS11 interacts preferentially with R7BP over G alpha(oa) - Characterization of G beta 5-free RGS11 - Saleem, Yasar; Kim, Key-Sun (ACADEMIC PRESS INC ELSEVIER SCIENCE, 2009)
Regulator of G protein signaling 11 (RGS11) is the least characterized member of the R7 family of G gamma-like GGL domain-containing RGS proteins. All R7-RGS proteins of a variety of cell types are found in G beta 5-containing complexes that exhibit a number of unique functional properties. However, presence of G beta 5 reduced the affinity of R7-RGS7 for G alpha subunits, also only RGS7 bound to Muscarinic M3-Receptor, but the G beta 5-RGS7 dimer did not, making it difficult to study differential interaction of R7-RGS proteins. Here, we report the successful purification of functionally intact, G beta 5-free recombinant RGS11 (rRGS11), obtained by expressing N- and C-terminally truncated form of RGS11 in Escherichia coli BL 21 (DE3), that differentially interact with R7BP and G alpha(oa). rRGS11 was capable of interacting with G alpha(oa) and R7BP (RGS7 family binding protein) with equilibrium dissociation constants (K-D) of 904 (+/- 208) W, and 308 (+/- 97) nM, respectively. It also induced several-fold increase in the GTPase activity of G alpha(oa). The binding of rRGS11 was differential with a binding preference for R7BP over G alpha(oa) implying extended roles of R7BP. In addition, we identified a novel interaction between G(oa) and R7BP with a K-D of 592 (+/- 150) nM. The production of stable and functional rRGS11 would provide chances to discover more functions of RGS11 yet to be identified. (C) 2009 Published by Elsevier Inc.